The is and ought of the Ethics of Neuroenhancement: Mind the Gap - Forlini, Cynthia; Hall, Wayne (Frontiers in Psychology, 2016)
Ethical perspectives on the use of stimulants to enhance human cognitive performance (neuroenhancement) are polarized between conservative and liberal theories offering opposing advice on whether individuals have a right to use neuroenhancers and what the social outcomes of neuroenhancement might be. Meanwhile, empirical evidence shows modest prevalence and guarded public attitudes towards the neuroenhancement use of stimulants. In this Perspective, we argue that the dissonance between the prescriptions of ethical theories (what ought to be) and empirical evidence (what is) has impaired our understanding of neuroenhancement practices. This dissonance is a result of three common errors in research on the ethics of neuroenhancement: (1) expecting that public perspectives will conform to a prescriptive ethical framework; (2) ignoring the socio-economic infrastructures that influence individuals’ decisions on whether or not to use neuroenhancement; and (3) overlooking conflicts between fundamental ethical values namely, safety of neuroenhancement and autonomy. We argue that in order to understand neuroenhancement practices it is essential to recognize which values affect individual decisions to use or refuse to use neuroenhancement. Future research on the ethics of neuroenhancement should assess the morally significant values for stakeholders. This will fill the gap between what ought to be done and what is done with an improved understanding of what can be done within a particular context. Clarifying conflicts between competing moral values is critical in conducting research on the efficacy of substances putatively used for neuroenhancement and also on neuroenhancement practices within academic, professional and social environments.